Training on Designing Digital Learning Media for MGMP Biology Teachers at SMA/MA Dharmasraya - Najmiatul Fajar; Aidhya Irhash Putra; Diyyan Marneli; Rina Delvita; M Haviz; Roza Helmita; Dwi Rini Kurnia Fitri; Nurlaila Nurlaila (Jurnal Masyarakat Religius dan Berwawasan, 2022)
Learning media is one component of learning that is very important in achieving learningobjectives. Along with the development of the times, teachers must also be able to adjust theircompetence in creating technology-based media. One of the technology-based media is digital learningmedia. Through applications such as Canva, Flip Pdf Professional and Augmented Reality, teachers cancreate interesting learning media that can help achieve learning goals effectively. The method used inthe training in designing digital learning media for MGMP Biology teachers at SMA/MA Dharmasrayaconsists of the preliminary stage, namely analyzing problems and preparing training materials, theimplementation stage, by guiding teachers in designing digital media, and evaluation throughobservation and distributing questionnaires. Then the evaluation results will be described as aconclusion from the implementation of this training. Through this training, it can be concluded that thematerial provided during the training has been able to equip the biology MGMP teachers of SMA/MADharmasraya in making digital media, the trainees are very enthusiastic when studying the materialprovided, and based on the results of the questionnaire this training has gone well so it is recommendedthat the implementation This training is sustainable.